Risk factors associated with purchasing pesticide from shops for self-poisoning: a protocol for a population-based case–control study. Issue 5 (20th May 2015) - Weerasinghe, Manjula; Konradsen, Flemming; Eddleston, Michael; Pearson, Melissa; Gunnell, David; Hawton, Keith; Jayamanne, Shaluka; Pabasara, Chathurani; Jayathilaka, Tharidu; Dissanayaka, Kalpani; Rajapaksha, Sandamali; Thilakarathna, Prasanna; et al.
Abstract : Introduction: Pesticide self-poisoning is one of the most frequently used methods of suicide worldwide, killing over 300 000 people annually. Around 15–20% of pesticide self-poisonings occur soon after the person has bought the pesticide from a shop. We aim to determine the characteristics of individuals who purchase pesticides directly from shops and how they differ from individuals who access pesticides from other sources such as home, home garden or farmland. This information will help inform possible vendor/shop-based intervention strategies aimed at reducing access to pesticides used for self-harm. Methods and analysis: This study will investigate risk factors associated with purchasing pesticides for acts of self-poisoning from pesticide shops, including cases identified over a 9-month period using a population-based case–control group approach. Four interviewer-administered data collection tools will be used for this study: a semistructured questionnaire, Beck Suicidal Intent Scale (SIS), Clinical Interview Schedule—Sinhalese version (CIS-Sn) and Alcohol Use Disorders Identification Test (AUDIT). Each case (expected n=33) will be compared with two groups of individuals: (1) those who have self-poisoned using pesticides from the home, home garden or farmland and (2) those who bought pesticides from the same shops as the above cases, but not did not self-poison. Logistic regression models will be used to identify risk factors of purchasing pesticides for self-poisoning from shops. Ethics and dissemination: The study has received ethical approval from the Ethical Review Committee of the Faculty of Medicine and Allied Sciences, Rajarata University of Sri Lanka. A sensitive data collection technique will be used and ethical issues will be considered throughout the study. Results will be disseminated in scientific peer-reviewed articles.